The influence of community factors in the implementation of community-based interventions to improve antenatal care: a qualitative study based on the IMCHA programme in Tanzania - Chakupewa Joseph; Stephen O. Maluka (BMC, 2021)
Plain English Summary Increasing uptake of antenatal care services is crucial for improving maternal and child health. One of the strategies that has been found to be relevant for improving uptake of antenatal care services in resource constrained countries especially in rural communities is implementation of community based initiatives. This study focused on the project that was implemented in Iringa region, Tanzania under the Innovating for Maternal and Child Health in Africa (IMCHA) program, which was implemented through community based initiatives. In order to understand community contextual factors that facilitated or constrained implementation of the IMCHA project, a participatory approach was applied to seek views from women groups as key project implementers and other stakeholders such as community leaders, male champions' religious leaders, health care providers and health facility governing committees. A total of one hundred forty six people were engaged in interviews and focused group discussions. Community readiness to adopt the interventions emerged as a determining factor for success of the project. Stakeholder engagement also enabled participatory implementation. The major constraining factors were the physical environment that made navigation through the villages difficult as well as negative feedback from family members. This study concludes that community readiness and participatory approaches can be enhanced by various aspects integrated in the initial designing of project activities. This strengthens the project support system critical for sustainability.